Peran Bahasa Arab Terhadap Peningkatan Kecerdasan Siswa - Aminuddin, Arpin; Yusnani, Yusnani; Nursholekha, Nursholekha; Mustofa, Syaiful (Prosiding Konferensi Nasional Bahasa Arab, 2023)
Arabic can increase student intelligence, because Arabic has a beautiful language structure, so students are required to be able to analyze every change in words, position, function and meaning. In this way, students will be trained to optimize their imagination to increase their intelligence. This research aims to determine the role of Arabic in increasing students' intelligence. This research uses a qualitative approach with descriptive methods. Data collection techniques use interviews and documents. The object of this research was students from the Imam al Hanafi Islamic boarding school, North Sumatra. The results of this research show that Arabic has a role in increasing student intelligence, as evidenced by three factors, namely the arguments of naqli and aqli, student learning outcomes, and Arabiyah musabaqah.